Offenses of Insults, Defamation, and Slander Versus Offenses of Trouble Juncto Offenses of Information Electronic Transactions - Youngky Fernando; Bella Agatha (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
This study wants to analyze the offense of defamation, defamation, defamation and slander against the impact of chaos on Juncto offenses on electronic transaction information. This research method uses normative legal research based on legal facts that have been ratified. The data collection method is in the form of in-depth interviews with key respondents to obtaining differentiated data so that the data is valid. Observations in the field to observe actual events regarding law enforcement. Documentation studies in the form of defamation law handbooks and archives are available as existing and objective results. Conclusion In the offense of insult, and defamation, as well as the offense of slander. Contempt Art 310 and Art 311. Is a Complaint Offense. The delict of lying caused uproar about Article 14 of the Delict of Fake News, and Article 15 of the Delict which is a Material Delict, namely the fulfillment of the elements of the offense and the occurrence of mass riots. Electronic information offense Electronic Transaction Information. (ITE). Article 45 paragraph (1) Juncto Article 27 paragraph (3) Offenses of Defamation and/or Defamation, and Article 45 paragraph (2) Juncto. As well as the Delict of Defamation Juncto Article 27 paragraph (3) and Article 45A paragraph (2) SARA Offenses. Juncto Article 28 paragraph (2) constitutes a Complaint Offense.